Alat Ukur Karakteristik Tanah Berbasis IoT untuk Tanaman Pangan (Padi, Jagung, Kedele) - Widianta, Moh. Munih Dian; Utomo, Denny Trias; Bety Etikasari; Jumiatun; Mahendra, Octavian Yudha (ReTII, 2022)
IoT or Internet of Things is a concept in which an object or objects are embedded with technologies such as sensors and software for the purpose of communicating, controlling, connecting and exchanging data through other devices for free, which are connected to the Internet. In this study, measuring instruments were designed, implemented and tested on IoT-based soil using the Fritzing application, implementation was carried out by assembling the Wemos D1 R1 microcontroller component, soil pH sensor, and DS18B20 temperature sensor, and implementing logic programming using Arduino IDE. From the results of testing the implementation of the tool according to the design, the Wemos D1 R1 Microcontroller used in this study has a drawback that it only has an operational voltage of 3.3v, while the Arduino Soil pH Sensor used requires an operational voltage of 5v. In hardware testing, especially in testing the Arduino Soil pH Sensor, it produced an error rate of 18.24%. This large error percentage is because the Arduino Soil Sensor operational voltage requirement of 5v is not met by the Wemos D1 R1 microcontroller which only has an operational voltage of 3.3v.